Optimization coverage conserving protocol with authentication in wireless sensor networks - Zeyu Sun; Longxing Li; Xuelun Li; Xiaofei Xing; Yuanbo Li (International Journal of Distributed Sensor Networks)
In the k -coverage process of target nodes, substantial data redundancy occurs, which leads to the phenomenon of congestion, reducing the network communication capability and coverage as well as accelerating network energy consumption. Therefore, this article proposes an Optimization Coverage Conserving Protocol with Authentication. This protocol provides a solution to obtain the largest coverage probability for multi-nodes. In the optimization and authenticated calculation, the protocol provides the calculation method and verification process of the expected value of multi-node coverage; when the moving target nodes are continuously covered, this protocol provides a process to solve for the focused target nodes; when there is redundancy coverage, this article provides a process to calculate the coverage probability when any sensor node is covered by a redundant node. Furthermore, through comparisons of the coverage quality and network lifetime with other algorithms, the performance indexes of this protocol have been substantially increased by the simulation experiment, which verified the effectiveness and viability of the protocol in this article.